Emerging lessons from the COVID-19 pandemic about the decisive competencies needed for the public health workforce: A qualitative study - Bashkin, Osnat; Otok, Robert; Leighton, Lore; Czabanowska, Kasia; Barach, Paul; Davidovitch, Nadav; Dopelt, Keren; Duplaga, Mariusz; Okenwa Emegwa, Leah; MacLeod, Fiona; Neumark, Yehuda; Raz, Maya Peled; et al. (Frontiers in Public Health, 2022)
The global COVID-19 crisis exposed the critical need for a highly qualified public health workforce. This qualitative research aimed to examine public health workforce competencies needed to face COVID-19 challenges and identify the gaps between training programs and the competency demands of real-world disasters and pandemics. Through a sample of thirty-one participant qualitative interviews, we examined the perspectives of diverse stakeholders from lead public health organizations in Israel. Grounded Theory was used to analyze the data. Six themes emerged from the content analysis: public health workforce's low professional status and the uncertain future of the public health workforce; links between the community and Higher Education institutions; the centrality of communication competencies; need to improve health promotion; the role of leadership, management, and partnership, and innovation in public health coherence. Increasing the attractiveness of the profession, professional and financial support, and improving the working conditions to ensure a sustainable and resilient PH system were deemed necessary. This paper describes and cultivates new knowledge and leadership skills among public health professionals, and lays the groundwork for future public health leadership preparedness programs.